2004
DOI: 10.3171/foc.2004.16.1.14
|View full text |Cite
|
Sign up to set email alerts
|

Minimally invasive spinal surgery: a historical perspective

Abstract: The concept of minimally invasive spinal surgery embodies the goal of achieving clinical outcomes comparable to those of conventional open surgery, while minimizing the risk of iatrogenic injury that may be incurred during the exposure process. The development of microscopy, laser technology, endoscopy, and video and image guidance systems provided the foundation on which minimally invasive spinal surgery is based. Minimally invasive treatments have been undertaken in all areas of the spinal axis since… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
44
1
6

Year Published

2005
2005
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(55 citation statements)
references
References 88 publications
(74 reference statements)
0
44
1
6
Order By: Relevance
“…59 To create a more homogenous patient cohort, studies involving the following procedures were excluded: interbody fusion, transperitoneal lumbar microdiscectomy, corpectomy, revision surgery, and lumbar microdiscectomy spanning more than one vertebral level. We included studies in which lumbar microdiscectomy was performed for degenerative indications and excluded those in which lumbar discectomy was performed to treat infection and tumor pathological processes.…”
Section: Inclusion and Exclusion Criteriamentioning
confidence: 99%
“…59 To create a more homogenous patient cohort, studies involving the following procedures were excluded: interbody fusion, transperitoneal lumbar microdiscectomy, corpectomy, revision surgery, and lumbar microdiscectomy spanning more than one vertebral level. We included studies in which lumbar microdiscectomy was performed for degenerative indications and excluded those in which lumbar discectomy was performed to treat infection and tumor pathological processes.…”
Section: Inclusion and Exclusion Criteriamentioning
confidence: 99%
“…Similar to stabilization procedures of the thoracolumbar spine, which have been proposed to reduce access-related morbidity as muscular denervation, atrophy, length of hospital stay, blood loss and postoperative pain [16,21,22], minimally invasive procedures for posterior cervical instrumentation represent the next logical step. Therefore, several authors reported minimally invasive posterior procedures for stabilization and decompression of the cervical spine [5,8,33,40,45]; however, the long-term benefit on clinical outcome remains to be proven. In this study, the feasibility and accuracy of percutaneous CPS placement using conventional fluoroscopy and three-dimensional fluoroscopy are presented and limitations as well as indications of this technique are discussed.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to stabilization procedures of the thoracolumbar spine with the objective to reduce access-related morbidity as muscular denervation and atrophy, length of hospital stay and blood loss [10,16,21,22,38,44], minimally invasive procedures for cervical instrumentation represent the next step to reduce accessrelated muscular trauma. Therefore, several authors reported minimally invasive posterior procedures for stabilization and decompression of the cervical spine [8,33,40,45]. However, this topic has not extensively investigated yet.…”
Section: Introductionmentioning
confidence: 99%
“…In order to prevent these complications, many authors have performed and popularized alternative less invasive surgical techniques. Nowadays, minimal access procedures are increasingly gaining popularity in spine surgery [15,33,45] but their use is poorly described in the treatment of cervical spine tumors [46]. The purpose of the present paper is to illustrate our experience with these minimally invasive approaches for the treatment of cervical schwannomas.…”
Section: Introductionmentioning
confidence: 99%